Semiquantitative chest computed tomography scoring system to estimate severity in pediatric community-acquired pneumonia - Huifeng Fan; Xuehua Xu; Wangchun Dai; Diyuan Yang; Senqiang Zeng; Qiang Zeng; Gen Lu (Frontiers in Pediatrics)
IntroductionA retrospective study assessed the utility of semiquantitative chest Computed tomography (CT) in diagnosing and determining the severity of community acquired pneumonia (CAP) in children.MethodsThe study included pediatric patients with CAP from January 2019 to December 2023. A semiquantitative chest CT scoring system was used based on the extent of lung inflammatory lesions and hydrothorax. The inter-rater reliability between two observers was assessed. The score was then correlated with laboratory results, identified pathogens, and patient prognosis. Receiver operating characteristic (ROC) analysis was employed to evaluate the diagnostic accuracy of the score for identifying severe cases.ResultsThe study included 426 patients, with 186 severe cases (43.66%). The intragroup correlation coefficient (ICC) value of the two observers was 0.957 (95% Cl: 0.944-0.970). The results showed a positive correlation between chest CT scores and neutrophil percentage, neutrophil count, and C-reactive protein, procalcitonin, lactate dehydrogenase, and fibrinogen levels and a negative correlation between lymphocyte count and hemoglobin and albumin levels (P < 0.001). The patients with coinfection had higher scores than those with single infections (P < 0.05). There was a positive relationship between the score and fever duration and length of stay (P < 0.001). The area under the curve (AUC) of chest CT score for diagnosing severe cases was 0.805. A score cutoff of >3 had 64.52% sensitivity and 84.17% specificity.ConclusionIt is practicable and effective that a semiquantitative chest CT scoring system be used for estimating condition and evaluating prognosis of pediatric CAP.